Particle size characteristics of a palm oil mill boiler flyash - Mohd. Yusoff, Mohd. Rashid (UTM, 1987)
A size distribution measurement of a palm oil mill fly ash samples collected at the stack exit downstream of a mill boiler was made. Results show that the geometric mean particle size was between 1.28 to 1.68 micron. Almost 90% of the fly ash falls well below 4 um size diameter and this could pose potential health hazard since these pasticles are in the respirable particulate size region. Other significant characteristics of the fly ash particulate are further discussed in the paper.